Gender Differences in Preferences - Croson, Rachel; Gneezy, Uri (Journal of economic literature, 2009)
This paper reviews the literature on gender differences in economic experiments. In the three main sections, we identify robust differences in risk preferences, social (other-regarding) preferences, and competitive preferences. We also speculate on the source of these differences, as well as on their implications. Our hope is that this article will serve as a resource for those seeking to understand gender differences and to use as a starting point to illuminate the debate on gender-specific outcomes in the labor and goods markets.